Risk factors for post-stroke spasticity: a retrospective study - Chuanxi Zhu; Lingxu Li; Long Qiu; Long Qiu; Guangcheng Ji; Guangcheng Ji (Frontiers in Neurology)
BackgroundPost-stroke spasticity (PSS) is a common complication after stroke and is an important cause of high rates of disability after stroke. At present, modern medicine has made great progress in the treatment of PSS, ‘early detection, early treatment’ has become a general consensus for the treatment of PSS in the clinic. Clarifying the risk factors of PSS can help to detect and treat the functional disorders caused by PSS at an earlier stage.MethodsThis is a retrospective study. 436 stroke patients who visited the Neurology Department of the Third Affiliated Clinical Hospital of Changchun University of Chinese Medicine from June 2020 to November 2020 were selected as study subjects, and finally 257 patients were included in the final analysis, and divided into 101 cases with spasticity and 156 cases without spasticity, depending on whether or not the stroke victim had a spasm at the time of admission.ResultsThe multivariate regression analysis showed that basal ganglia as the cerebral hemorrhage or infarction site (OR = 4.930, 95%CI = 2.743–8.86, p = 0.000), cerebral hemorrhage or infarction volume (OR = 1.087, 95%CI = 1.016–1.164, p = 0.016) and NIHSS scores (OR = 1.232, 95%CI = 1.089–1.393, p = 0.001) are independent influencing factors and independent risk factors for spasticity (p < 0.05). A risk prediction model for spasticity in stroke patients is derived with the multivariate logistic regression analysis Logit (P) = 1.595 * Basal ganglia +0.084 * infarct volume + 0.208 * NIHSS scores – 2.092. An evaluation of the goodness of fit using the ROC curve showed AUC (95% CI) = 0.786 (0.730–0.843), an indication of a high degree of model fit.ConclusionIndependent risk factors for Post-stroke spasticity include basal ganglia as the cerebral hemorrhage or infarction site, cerebral hemorrhage or infarction volume and NIHSS scores.